Universal, school-based transdiagnostic interventions to promote mental health and emotional wellbeing: a systematic review - Peng Wang; Zhaoqi Wang; Shuiwei Qiu (Child and Adolescent Psychiatry and Mental Health, 2024)
Abstract Objective This systematic review aims to evaluate the effectiveness of universal school-based transdiagnostic interventions in promoting the mental health of children and adolescents. It compares and discusses interventions targeting the prevention of mental disorders versus the promotion of mental health. Additionally, the roles of teachers and psychologists as intervention conductors are examined. Methods A comprehensive search of the Psycinfo, Pubmed, and Web of Science databases was conducted without any time restrictions to identify relevant literature on universal school-based transdiagnostic interventions promoting children and adolescents' mental health. Results and discussion The findings reveal that universal school-based transdiagnostic promotion/prevention programs have a small to medium overall effect size. These interventions demonstrate a broad coverage of different aspects of children and adolescents' mental health. However, the relative effectiveness of teacher-led versus psychologist-led interventions remains unclear. Interventions focused on preventing mental disorders exhibit a higher effect size, albeit on a narrower range of mental health aspects for children and adolescents. Significance This study enhances our understanding of universal school-based transdiagnostic interventions and their impact on children and adolescents' mental health. Further research is needed to elucidate the comparative efficacy of teacher-led and psychologist-led interventions and to explore the specific dimensions of mental health targeted by these interventions.